FACTORS LIMITING DEVELOPMENT AND MANAGEMENT IN MODERNFARMS: CASE STUDY IN SOUTH-EAST POLAND - Jadwiga Topczewska; Joseph Ohimor (Annals of the Polish Association of Agricultural and Agribusiness Economists)
Contemporary farms are enterprises that operate according to market principles, the developmentof which is influenced by a number of factors. The aim of the paper was to identify factors that inhibitthe development of farms located in south-eastern Poland. The study made use of findings obtained inresearch by the Central Office of Statistics (GUS) concerning the structure of agricultural farm holdingsin 2016. Factors inhibiting the development of agricultural farms located in south-eastern Poland include,first and foremost, unfavourable agrarian patterns, few farm owners with agricultural training as well aslack of appropriate managerial skills needed for effective management in modern agricultural enterprises.Only about 20% of farm managers were below 40 years of age. About 15% of owners indicated that over50% of farm incomes were from non-agricultural activities.